Efektifitas Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (Ts-Ts) terhadap Hasil Belajar Matematika Siswa Kelas III Sekolah Dasar - Tri Putri Nurwijayanti; Sukardi; Rury Rizhardi (Universitas PGRI Palembang, 2023)
This study aims to determine the effect of the learning model on the mathematics learning outcomes of students who study using the Two Stay-Two Stray learning model for class III SD Negeri 5 Palembang. Learning is essentially active and skilled. This research is a quantitative research with the type of experimental research and used a pretest-posttest control group design. The research sample used is saturated sampling technique. The subjects in this study were students in class IIIA and IIIB whose grades were relatively low but had not yet achieved the KKM score. Data collection is done by observation, test, documentation. The data obtained were analyzed using the Normality Test, Homogeneity Test and Independent Test to determine the application of using the Two Stay-Two Stray learning model. Based on the results of the study, there was an increase in learning outcomes for students in the experimental class through a mathematics learning test using the Two Stay-Two Stray learning model with a pretest score of 56 and a posttest score of 78 with the complete category. While the control class does not use the Two Stay-Two Stray learning model with a test score of 52 pretest and 65 posttest scores with incomplete categories. This is also reinforced by the results of the hypothesis test t test (independent t test) that the value of t count is 12.255 <2.021, so it can be concluded that there is an Effectiveness of the Two Stay Two Stray (Ts-Ts) Cooperative Learning Model on Mathematics Learning Outcomes of Grade III SDN Students 5 Palembang. Keywords: The Effectiveness of Learning Models, Two Stay Two Stray Types (Ts-Ts), Mathematics Learning Outcomes